Madly in love with me : the daring adventure of becoming your own best friend - Arylo, Christine, 1971- (New World Library, 2012)
"A coach and workshop leader offers advice, encouragement, and exercises for improving self-esteem, self-empowerment, and self-acceptance"--Provided by publisher.